Evaluation of lumbar spine load by computational method in order to acknowledge low-back disorders as occupational diseases - Hlávková, Jana; Lebeda, Tomáš; Tichý, Tomáš; Gaďourek, Petr; Urban, Pavel; Nakládalová, Marie; Laštovková, Andrea; Fenclová, Zdeňka; Ridzoň, Petr; Ehler, Edvard; Richter, Milan; Pešáková, Lenka; et al. (Central European Journal of Public Health, 2016)
AIM: The aim of the study was to develop a computational module for the prediction of compressive force on the L4/L5 disc suitable for use in field settings. METHOD: The value of compressive force is intended to be used as a proxy measure of the mechanical burden of low-back when performing work activities. The compressive force predicted by the module in a particular worker should be compared with the NIOSH limit value of 3,400 N for the assessment of lumbar spine load during manual lifting tasks. Exceeding the limit will be considered as the fulfilment of "hygienic criterion" that should be met to acknowledge low-back disorder as an occupational disease. To develop the computational module we used the ergonomic software TECNOMATIX Classic Jack taking into account the anthropometric parameters of a worker and ergonomic parameters of his/her work activity. RESULTS: We calculated compressive forces on the L4/L5 disc in about 1,300 simulated combinations of various factors influencing compressive force. Parameters which turned out to be crucial for the compression of L4/L5 disc were included in the computational algorithm. CONCLUSION: Our study was primarily aimed at the assessment of lumbar disorders as occupational diseases. Moreover, the study can contribute to the recommendation of preventive measures to decrease health risks in occupations associated with the overload of low-back region. The graphic maps generated by the computational module enable a fast and exact analysis of particular job.
Keywords: biomechanika; Lumbar Vertebrae; Predictive Value of Tests; lumbalgie; National Institute for Occupational Safety and Health, U.S.; bederní obratle; Weight-Bearing; Česká republika; Spojené státy americké; Software; Ergonomics; Work Capacity Evaluation; antropometrie; United States; národní institut pro bezpečnost a zdraví při práci (USA); Czech Republic; zatížení muskuloskeletálního systému; postura těla; Posture; ergonomie; posuzování zdravotní způsobilosti; prediktivní hodnota testů; Anthropometry; nemoci z povolání; software; Occupational Diseases; Low Back Pain; Biomechanical Phenomena; lidé; Humans; algoritmy; Algorithms